Differential progression of renal scarring and determinants of late renal recovery in sustained dialysis dependent acute kidney injury secondary to myeloma kidney. Issue 10 (27th September 2010) - Basnayake, Kolitha; Cheung, Chee Kay; Sheaff, Michael; Fuggle, William; Kamel, Dia; Nakoinz, Sandra; Hutchison, Colin A; Cook, Mark; Stoves, John; Bradwell, Arthur R; Cockwell, Paul
Abstract : Background: Most cases of dialysis-dependent acute kidney injury due to myeloma cast nephropathy do not recover renal function. Renal biopsy typically shows cast formation, direct tubular injury and interstitial inflammation caused by nephrotoxic monoclonal free light chains (FLC). Established scarring at presentation is rarely severe. There is little data on in situ evolution of renal injury. Aims: To conduct a detailed histological study of four patients with cast nephropathy. Methods: Cast nephropathy was confirmed by renal biopsy. Treatment consisted of chemotherapy and high cut-off dialysis to maximise extracorporeal removal of FLC and reduce renal toxicity. All four patients remained dialysis dependent at 6 weeks, at which time they underwent a further biopsy. Results: Three patients achieved independence from dialysis. Six-week biopsies showed differential changes in chronic damage from no progression, to accelerated progression of scarring from 10% to 42%, despite a rapid and sustained fall in FLC in all patients. In three patients there was a major reduction in intratubular cast numbers; these patients subsequently recovered renal function. In one patient who continued to have high cast formation at 6 weeks there was no subsequent renal recovery. Conclusions: Some FLC clones can promote rapid renal scarring. Significant reductions in cast formation on repeat biopsy may identify the potential for late renal recovery. Early diagnosis and treatment may prove crucial in determining renal recovery. Patients who have not recovered renal function after a period of treatment may be usefully reassessed by repeat biopsy for quantitative analysis of chronic damage and cast numbers.